Radiator-type solar heating system with phase change material for residential thermal comfort - Kléber Janampa Quispe; Octavio Cerón Balboa; Oswaldo Morales Morales; Julio Oré García; Hugo David Calderón Vilca (International Journal of Renewable Energy Development, 2026)
This paper presents the design, construction, and experimental thermal evaluation of a modular solar heating system that integrates heat collection, storage, and emission into a single compact unit. The prototype consists of a flat-plate solar air collector directly coupled to a radiator-type thermal storage module. The central innovation lies in the use of paraffin as a phase change material (PCM), encapsulated in twelve finned aluminum tubes. This configuration enables the storage unit to function simultaneously as a passive heat exchanger, ensuring a uniform and sustained release of the accumulated energy. Experimental results, obtained under a solar irradiance of 950 W/m², showed that the air temperature at the collector outlet exceeded 70 °C. During the discharge phase, the indoor ambient temperature remained within the thermal comfort range (20.5 °C–23.6 °C) for up to six hours, maintaining a 3–4 °C temperature difference relative to the outdoor environment. The latent heat storage capacity of the PCM effectively mitigated indoor temperature fluctuations, contributing to stable comfort conditions. In conclusion, the proposed system represents a significant innovation in passive solar energy technology, integrating the functions of collector, accumulator, and radiator into a low-cost, easily replicable modular device. Its constructive simplicity and thermal efficiency position it as a viable and sustainable solution for residential heating in cold climates and rural or hard-to-reach areas with limited energy access.